The adjustment of life history strategies drives the ecological adaptations of soil microbiota to aridity - Chaonan Li; Haijun Liao; Lin Xu; Changting Wang; Nianpeng He; Junming Wang; Xiangzhen Li (Molecular Ecology, 2022)
Soil microbiota increase their fitness to local habitats by adjusting their life history strategies. Yet, how such adjustments drive their ecological adaptations in xeric grasslands remains elusive. In this study, shifts in the traits that potentially represent microbial life history strategies were studied along two aridity gradients with different climates using metagenomic and trait‐based approaches. The results indicated that resource acquisition (e.g., higher activities of β‐ d ‐glucosidase and N ‐acetyl‐β‐ d ‐glucosidase, higher degradation rates of cellulose and chitin, as well as genes involved in cell motility, biodegradation, transportation and competition) and growth yield (e.g., higher biomass and respiration) strategies were depleted at higher aridity. However, maintenance of cellular and high growth potential (e.g., higher metabolic quotients and genes related to DNA replication, transcription, translation, central carbon metabolism and biosynthesis) and stress tolerance (e.g., genes involved in DNA damage repair, cation transportation, sporulation and osmolyte biosynthesis) strategies were enriched at higher aridity. This implied that microbiota have lower growth yields but are probably well primed for rapid responses to pulses of rainfall in more arid soils, whereas those in less arid soils may have stronger resource acquisition and growth yield abilities. By integrating a large amount of evidence from taxonomic, metagenomic, genomic and biochemical investigations, this study demonstrates that the ecological adaptations of soil microbiota to aridity made by adjusting and optimizing their life history strategies are universal in xeric grasslands and provides an underlying mechanistic understanding of soil microbial responses to climate changes.